Reflections on labour strategy in urban and regional governance - MacDonald, Ian; Wieditz, Thorben (Trade unions and regions: better work, experimentation, and regional, 2022)
This chapter examines how unions have joined in cross-class territorial alliances to shape labour markets, employment relations, public services, and housing markets across a variety of sectors. It analyses various campaigns where attempts were made to make labour markets and employment practices conform to a model that is more conducive to union organisation and bargaining. These initiatives occur in a challenging environment, characterised by the loss of ‘good jobs’ with deindustrialisation and the rise of new business models in the service economy. The authors produce a map of the terrain which would permit decision-making in full view of the variety of strategies available to unions. They identify the common ground between unions and other class actors, class fractions, and the local state, to understand how it is possible for trade unions to advance their priorities in urban and regional governance. The chapter concludes with a reflection on the limits of cross-class alliances and the potential for union strategies beyond the reproduction of capitalist social relations.
Keywords: ok